The Role of Teachers in Planning Preschool Education - Avezova Maxliyo Sultonnazir qizi (Genius Journals, 2023)
The teacher's job as a planner and implementer of learning is one that must be fulfilled. The administrator position is one of them. The administrator is one of the teacher's tasks in organizing a sequence of learning activities for a specific amount of time while adhering to the principles of manufacture and organization. However, instructors are hampered in developing time-consuming learning plans, resulting in a lack of concentration in teaching and learning activities. As a result, the goal of this research is to determine the function of teachers in early childhood learning planning. The research method used is descriptive quantitative with the analysis of the frequency distribution presentation obtained from a questionnaire given to the teacher as a data collection technique. The results showed that 62.5% of the teachers strongly agreed, 31.25% answered that the teachers agreed and 6.25% answered hesitantly. Therefore, it can be concluded that the teacher strongly agrees that the role of the teacher as administrator is more widely used so that it has an impact on the role of the teacher as the implementation of the learning process as a result of the analysis of the role of the teacher as a whole in the process of the educational series.
Keywords: educational; whole; concluded; learning